Pregnancy in pulmonary arterial hypertension. (December 2016) - Olsson, Karen M.; Channick, Richard
Despite advanced therapies, maternal mortality in women with pulmonary arterial hypertension (PAH) remains high in pregnancy and is especially high during the post-partum period. However, recent data indicates that morbidity and mortality during pregnancy and after birth have improved for PAH patients. The current European Society of Cardiology/European Respiratory Society guidelines recommend that women with PAH should not become pregnant. Therefore, the risks associated with pregnancy must be emphasised and counselling offered to women at the time of PAH diagnosis and to women with PAH who become pregnant. Early termination should be discussed. Women who choose to continue with their pregnancy should be treated at specialised pulmonary hypertension centres with experience in managing PAH during and after pregnancy. While pregnancy is not recommended in PAH, there is increasing experience in managing PAH in pregnant women http://ow.ly/N6b2305Aur3